The representation of the concept “Motherland” in Rasul Gamzatov’s works and their translation into English. - Ismatullayeva, Iroda (Журнал иностранных языков и лингвистики, 2023)
The given article discusses the representation of the concept “Motherland” in Rasul Gamzatov’s works and their translation into English. The aim of our research is to identify the features of the interpretation of "“Motherland " concept in Rasul Gamzatov’s poems into English. The research material was the corpus of literary texts from the collection of R. Gamzatov "Selected poems. In Russian and English"